RESEARCH ON FATIGUE PERFORMANCE TEST AND LIFE PREDICTION FOR STATOR RUBBER OF PCP - ZU HaiYing; GENG ChunLi; LI DaQi; SONG YuJie (Jixie qiangdu, 2018)
The rubber stator of PCP used for oil recovery is studied in this paper,Through the fatigue tension test of stator rubber material,establish of stator rubber S-N curve; The analysis of the finite element mechanical properties of PCP,determine the most likely fatigue failure position of screw pump is near the high pressure chamber spiral sealing belt; Prediction of fatigue crack formation life of stator rubber of PCP by Fe-safe,determine the the minimum fatigue crack formation life and safety factor of each model of the stator rubber of PCP,and it decreases with the increase of chamber pressure,And the relation between the fatigue crack formation life and the chamber pressure of the rubber stator is obtained.